Stakeholder participation in surface water and groundwater quality management in the Waterberg area: Limpopo Province, South Africa - Cornelus, Lesley-Ann Jolene (My University, 2018)
The aim of this research was to assess the status of water quality in a selected area of the Waterberg over a twenty-year period and to gain insight into the perceptions of stakeholders about water management. The objectives were met through the comparison of historical water quality variable records for various water uses, by measuring the level of stakeholder commitment in water quality measurement and verifying a relationship between the two approaches. This study focuses on measuring the extent of different stakeholders’ involvement in the management and decision-making processes of water quality in the Waterberg region of Limpopo province, which is encouraged by the formulation of South African policies. The specific area of interest is in the north-western part of the Waterberg. There are three distinct settlements, Lephalale, Marapong and Steenbokpan, located in the Lephalale Local Municipality. Close by are major industrial and mining activities from Eskom’s Matimba and Medupi power stations, and Exxaro’s Grootegeluk Coal Mine. To address the specific research questions and objectives for this study, two approaches were necessary: A quantitative approach that required surface water and groundwater data from 1995 to 2015, to determine the quality of water, and a qualitative approach that comprised of the distribution of 20 questionnaires in the residential areas, and 15/20 successful pre-selected individual interviews, to assess the different levels of stakeholder participation. Each approach presented its own challenges. For example, the water quality data provided were incomplete, which created limitations in the interpretation and during the questionnaire distribution, time constraints and language preferences, though anticipated amongst different social groups, there was difficulty communicating the concept of the study. Also, during the planning phase of selecting interviewees, there was a lack of interest in the study from environmental consultants, who are vital role players in the environmental status of the area. The water quality data indicated that pH levels in the surface water sites have remained steady and are not significantly different from one another. The results from the one groundwater site, reveals that there is a significant difference between the pH levels of surface water and groundwater which is to be expected. The results also suggest that the high concentration of ammonium, phosphate and nitrate midstream in the Mokolo River are related to the waste water being discharged mid-stream into the river via a pipeline. The high concentrations of sodium and potassium in the groundwater site are linked to the interaction time with the surrounding geology and the overall EC levels correspond with the fluxes in sodium in the groundwater site resulting in the significant difference in EC between the surface water and the groundwater sites. No data were available for the midstream site. The questionnaire results indicate that there’s limited stakeholder involvement in water quality management from participants in Steenbokpan and Marapong, which are socio-economically disadvantaged areas, when compared with Lephalale, a more affluent area. In contrast to Lephalale, Marapong and Steenbokpan residents are less educated, have higher unemployment numbers, and have restricted access to water related information, and electricity, water and sanitation services. In the overall area, there is also a 30% unawareness amongst general water users about the topic of water pollution, but again it is mostly from participants in Steenbokpan and Marapong. The interview results signified a higher level of stakeholder involvement in water quality management from individuals in influential positions. This, however, does not mean that water related issues in the area are adequately addressed. Interviewees revealed that there is a lack of funding, skills, infrastructure, manpower and competence. There is also an apparent inequality with regards to water access to informal settlements, farmers and rural villages. Additionally, there is a high level of dependency on Eskom and Exxaro, rather than the local municipality, to provide its water users with proper water services. The dependency on Eskom and Exxaro is largely due to their high level of influential development. Improvements and maintenance on basic service from these structures to the surrounding communities form part of their offset programmes to continue major development in the area. Due to the large difference of the qualitative and quantitative approaches, it was difficult to prove how one supports the other, even though, on its own, both are crucial components in water quality management practices. Even though the water quality data provide more reliable support on the condition of surface- and groundwater in the Waterberg, the social aspect (partially revealed through the subjective view of the general users who completed the questionnaire) is required to determine the community’s relationship with water use and to identify management practices through stakeholders responsible for them.
A Research Report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science, 2018
Keywords: Groundwater--Quality--South Africa; Water quality--South Africa--Limpopo; Water--Analysis